Evaluasi Instalasi Pengolahan Air Limbah Industri Kimia PT X - Yalka Sabilla; Eka Wardhani (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The wastewater treatment plant of PT X, a chemical polymer industry, was evaluated to assess its performance in treating wastewater to meet industrial environmental quality standards. This evaluation includes an analysis of effluent quality based on BOD, COD, TSS, TDS, pH, and temperature parameters. Secondary data from PT X's laboratory testing showed non-compliance with standards based on the Minister of Environment Regulation Number 05 of 2014, particularly for COD and BOD parameters. The efficiency of the wastewater treatment plant in reducing parameters was COD 97.7%, BOD 97.7%, TSS 99%, and a TDS value of -289.3%. The design evaluation showed that several treatment units, such as the coagulation-flocculation tank, were located in the same unit and had the same speed. Additionally, the coagulation detention time exceeded the design criteria by 11,833.2 seconds. This causes wastewater treatment to not function optimally. To improve the performance of the WWTP, it is recommended to adjust the volume of some treatment units, optimize operational parameters, and conduct regular monitoring to ensure the system continues to operate optimally.